Obtaining structured clinical data from unstructured data using natural language processing software. (2017) - Lacey, Arron S; Fonferko-Shadrach, Beata; Lyons, Ronan A; Kerr, Mike P; Ford, David V; Rees, Mark I; Pickrell, Owen W
No abstract available